EFFECTS OF BLACK SEEDS EXTRACTS SUPPLEMENTATION ON IFNΓ LEVEL OF MULTIBACILLARY LEPROSY PATIENTS RECEIVING WHO-MDT - Primasthi Anggraeni; R. Sri Djoko Susanto; Meilien Himbawani; Retno Indar Widayati (Faculty of Medicine Diponegoro University, 2017)
Background: Multibacillary leprosy patients exhibit a defective CMI response to M. leprae thereby causing a high bacillary load and lots of skin lesions, making untreated multibacillary patients becoming main reservoir and transmission of M.leprae. Th2 cytokines like IL-4, IL-5 and IL-10 elevated anc becoming characteristic of lepromatous or multibacillar patiens, with low level of Th1 cytokines, including IFN-g. Several studies showed that black seeds enhanced the production of IFN γ , posses potent potentiating effects on the CMI/ stimualtory effect on Th1 cells, while posses suppressor effects on humoral immunity/ inhibitory effect on Th2 cells. The purpose of this study is to know the effects of black seeds extract supplementation on IFN γ level of multibacillary leprosy patients. Methods: this study is experimental research with randomized controlled trial design. A sample of 44 patients was randomized into 2 groups: (i) placebo group, receiving WHO-MDT and palcebo, (ii) black seed goup, receiving WHO-MDT and black seed extracts. The independent variable was the WHO-MDT plus black seed supplementation (3000 mg), and WHO-MDT plus placebo given for 2 months . The dependent variable was IFN γ level. Results: Mean level of IFN γ before and after study from black seed groups was significantly different (p<0,0001), and mean delta value of black seed group was significantly superior (p=0,005/ p<0,05) to that of placebo. Conclusion: supplementation with black seeds extracts can enhance IFNγ production of multibacillary leprosy patients. Keywords: MB Leprosy, black seeds extract, Nigella sativa, IFNγ